Canine tarsal gland epitheliomas and adenomas: a retrospective study of 290 cases in Brazil - Werner, Juliana; Moura, Christiane M. C.; Werner, Pedro R.; Montiani-Ferreira, Fabiano (Brazilian Journal of Veterinary Pathology, 2017)
A total of 290 cases of tarsal gland adenomas and epitheliomas from canine patients were analyzed to determine the frequency and to better characterize their histopathological features. Tissue samples were examined in two veterinary pathology laboratories in Curitiba, Brazil, which receive samples from all over the country. Tarsal epitheliomas were significantly more frequent than tarsal adenomas (77.9% and 20.7%, respectively). In four cases (1.4%), the lesion contained both types of neoplasms. A total of 39 breeds were represented. The most common breeds were: English cocker spaniel (12.4%), poodle (10.3%) and Labrador retriever (9.3%). Mixed breed dogs represented 13.1% of the total. The upper eyelids were most commonly affected (65.2%), males and females were equally represented and there did not appear to be a predilection for either side of the face. Mitotic figures were most common in epitheliomas. The pigmented subtype was the most common form of epithelioma (59.7%). Whereas within the adenomas, the classic subtype (without inflammation or pigmentation) was the most common form (61.7%); and the inflamed subtype was also highly represented (20.0%).